The Effect of Principal Leadership and Teacher Performance on the Quality of Education at Junior High School - Suhartono Tono; Sartiah Yusran; Sahlan Sahlan (Halu Oleo University, 2022)
The quality of education is the ultimate goal of a teaching and learning process. This study aimed to examine the extent to which principal leadership and teacher performance could affect the quality of education at Junior High School level, both individually and concurrently. The research was conducted in Junior High School in Konawe regency, Southeast Sulawesi. The primary data was collected from 88 respondents. This study revealed that: 1) there is a significant effect of principal leadership on the quality of education at Junior High School; 2) there is a significant effect of teacher performance on the quality of education; 3) there is a significant simultaneous effect of principal leadership and teacher performance on the quality of education. The principal leadership variable and teacher performance explained 30,8% of the total variance in quality of education. Thus, in order to improve the quality of education in general, principal and teachers should develop their professional skills.